The Shariʻa history, ethics and law - Sajoo, Amyn B. (Muslim heritage series, 2018)
Why is the term shari'a - the mention of which conjures up images of a politicised religion in many parts of the world - understood in the ways that it is today? For Muslims and non-Muslims alike, much is read into this term, often with scant regard for its historical, cultural or theological underpinnings. This book offers an accessible account of the ideals and realities of the shari'a.